Coulomb explosion and steadiness of high-radioactive silicate glasses - Zhydkov, V. (Condensed Matter Physics, 2004)
The paper is devoted to the theoretical study of Coulomb explosion in silicate
glasses with low ionization potential under internal alpha-irradiation.
The phenomenon was studied in the way of computer simulation, namely
by the molecular dynamics (MD) method; parameters of the so-called lavalike
fuel-containing materials (LFCM), were chosen as input parameters
for the model due to its practical importance. LFCM are high-radioactive
glasses, which were formed during an active stage of a well known heavy
nuclear accident, occurred on Chornobyl NPP in 1986. Computer simulation
revealed that Coulomb explosion really may occur in the LFCMs and
leads to additional radiation damages under internal alpha-irradiation. The
total quantity of atomic displacements produced in the way of Coulomb explosion
from each alpha-particle track is 40000 to 80000, which exceeds
radiation damages from alpha-particle and heavy recoil nuclei altogether
(about 3500) more than one order. Ця робота присвячена теоретичному вивченню кулонівського вибуху в силікатних стеклах, що мають низький потенціал іонізації та перебувають під дією внутрішнього альфа-опромінення. Це явище було вивчено за допомогою комп’ютерного моделювання, а саме методом молекулярної динаміки (МД); параметри так званих лавоподібних паливомісних матеріалів (ЛПВМ), зважаючи на їх практичну значущість, були вибрані за вхідні параметри для цієї моделі. ЛПВМ – високорадіоактивні стекла, які утворилися впродовж активної стадії добре відомої важкої ядерної аварії, що відбулася на Чорнобильській АЕС в 1986. Комп’ютерне моделювання виявило, що кулонівський вибух дійсно може мати місце в ЛПВМ і призводить до додаткових радіаційних ушкоджень під дією внутрішнього альфа-опромінення. Загальна кількість атомних зміщень, утворених шляхом кулонівського вибуху від однієї альфа-частки, складає 40000 ÷ 80000, що більше за радіаційні пошкодження від альфа-частки і важкого ядра віддачі, взяті разом (близько 3500) більше, ніж на порядок.